2016
DOI: 10.1007/s00784-016-1876-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mouthwashes on the composition and metabolic activity of oral biofilms grown in vitro

Abstract: ObjectiveThe aim of this study was to determine the effect of an oxygenating mouthwash compared to two other established mouthwash products on bacterial composition and metabolic activity of oral biofilms in vitro.Material and methodsTwelve healthy subjects participated as donors. Plaque-saliva mixture inoculated biofilms were grown and treated with 3 different chemotherapeutic mouthwashes [amine fluoride/stannous fluoride (MD), oxygenating agent (AX), chlorhexidine 0.12 % (PA), and water (W)]. Effects of trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 38 publications
2
27
0
Order By: Relevance
“…Previous studies have reported that CHX exhibits a broad antibacterial spectrum against Gram-negative and Gram-positive bacteria, with the counts of total anaerobic and aerobic bacteria in dental biofilms reducing after treatment with CHX, with particularly large changes in Streptococci, Actinomyces, Bifidobacterium, and Veilonellae species. 21,22 In addition, the levels of caries-related species and anaerobes within cariogenic microcosm biofilms tended to be lower after exposing them to CHX. 23 The bacterial species identified previously could show that the RF depends on the growth conditions under the QLF lighting conditions, 24 which is attributed to the production of porphyrin compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported that CHX exhibits a broad antibacterial spectrum against Gram-negative and Gram-positive bacteria, with the counts of total anaerobic and aerobic bacteria in dental biofilms reducing after treatment with CHX, with particularly large changes in Streptococci, Actinomyces, Bifidobacterium, and Veilonellae species. 21,22 In addition, the levels of caries-related species and anaerobes within cariogenic microcosm biofilms tended to be lower after exposing them to CHX. 23 The bacterial species identified previously could show that the RF depends on the growth conditions under the QLF lighting conditions, 24 which is attributed to the production of porphyrin compounds.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, the reduction of GBI after the use of Ardox-X toothpaste can be due to the active oxygen in the toothpaste, which reduces the pathogens causing periodontal disease and bleeding. (12,13) The PI is more related to the way a person brushes and has less to do with toothpaste. (19,20) Therefore, in the present study, no significant difference was found in the PI.…”
Section: Discussionmentioning
confidence: 99%
“…Fernandez Y Mostajo et al investigated the antimicrobial potential of Ardox-X active oxygen in the form of mouthwash on oral bacteria and dental plaque. (12,13) They showed that Ardox-X changes the composition and metabolism of bacteria. The most susceptible are gram-negative anaerobic bacteria such as Prevotella, Fusobacterium, and Veillonella.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations